Nontuberculous Mycobacteria Lymphadenitis: A Case Report - Krantz, Amanda M (Cureus, 2016)
Atypical mycobacteria, also known as nontuberculous mycobacteria (NTM) includes acid-fast bacteria other than Mycobacterium tuberculosis. NTM can be isolated from a variety of environmental sources including water, food products, domestic animals, and soil; human exposure is typically from soil to the oral cavity and respiratory tract. Diagnosis of NTM is suspected in children less than five years old with subacute, unilateral, non-tender cervicofacial lymphadenitis in combination with a history of water exposure, penetrating injection, as well as negative routine cultures or response to antistaphylococcal and antistreptococcal antibiotics. The course of the disease is variable and can involve eruption of the lymph node and tract formation with drainage. Management of nontuberculous mycobacteria can include surgical and antimycobacterial therapy. We present a case of a two-year-old African American girl who presented to the clinic with anterior ear lobe and submandibular lymphadenitis due to suspected NTM.